2021
DOI: 10.3390/ijerph181910256
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Oral Hypofunction Tests, Age, and Sex

Abstract: Oral function declines in older individuals due to disease and age-related changes, making them vulnerable to oral and physical frailty. Therefore, it is important to manage the decline in oral function in older outpatients. Oral hypofunction is diagnosed by seven tests related to oral function, oral hygiene, oral moisture, occlusal force, oral diadochokinesis, tongue pressure, masticatory function, and swallowing function. However, sex or age were not factored into the current reference values of these tests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 27 publications
(49 reference statements)
5
23
0
Order By: Relevance
“…It is, therefore, necessary to consider a more appropriate intervention method and to further examine whether the reference value of low tongue‐lip motor function in oral hypofunction patients is high. In our recent previous research, 22 we found that the ODK score of dental outpatients decreased with increasing age, and prevalence in low tongue‐lip motor function patients was about 40%‐60%. Combined with the results of the current study, these findings suggest that the reference value of ODK should be reconsidered in the future.…”
Section: Discussionmentioning
confidence: 59%
“…It is, therefore, necessary to consider a more appropriate intervention method and to further examine whether the reference value of low tongue‐lip motor function in oral hypofunction patients is high. In our recent previous research, 22 we found that the ODK score of dental outpatients decreased with increasing age, and prevalence in low tongue‐lip motor function patients was about 40%‐60%. Combined with the results of the current study, these findings suggest that the reference value of ODK should be reconsidered in the future.…”
Section: Discussionmentioning
confidence: 59%
“…The management of oral hypofunction in dental outpatient clinics is one of the most important strategies for preventing oral frailty that dentists can implement into routine practice [ 8 , 9 ]. In Japan, oral hypofunction was first defined as a condition of complexly reduced oral functions, which satisfied three or more of the following seven oral examination criteria: oral hygiene, oral wetness, occlusal force, tongue-lip motor function, tongue pressure, masticatory function, and swallowing function.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, oral hypofunction has been included in the national medical insurance as a dental disease since 2018, and the need for oral health management of oral hypofunction in dental care is increasing. The prevalence of oral hypofunction increases with age [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The individual functions of the parts of the oral cavity work complementarily; therefore, the decline in oral function is not detected early and progresses gradually. Therefore, oral hypofunction (OHF) assessment has been proposed to quantitatively evaluate functional decline, which will lead to early detection of oral hypofunction [15,16]. The diagnosis of oral hypofunction is based on seven tests, and a diagnosis is made when the results of three or more of the seven tests are below normal values.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, oral hypofunction (OHF) assessment has been proposed to quantitatively evaluate functional decline, which will lead to early detection of oral hypofunction [15,16]. The diagnosis of oral hypofunction is based on seven tests, and a diagnosis is made when the results of three or more of the seven tests are below normal values.…”
Section: Introductionmentioning
confidence: 99%